Overview of the incidence of anemia on the Student Achievement Index of the D3 Nursing Study Program, Faculty of Medicine, Mulawarman University - Syahrun Syahrun; Fanny Metungku; Sholichin; Afifah Putri Wahyuni; Dwi Nopriyanto (Mulawarman Nursing Indonesia Journal, 2023)
Background: Anemia is a serious problem in the world, including in Indonesia. Anemia is a decrease in erythrocytes in the blood which results in reduced oxygen carriers into the body which can cause impaired growth of body cells and brain. If anemia occurs in adolescents, it can result in decreased fitness, concentration and decreased academic achievement. Purpose: Describe the relationship between anemia and student achievement index as an early detection of anemia events. Methods: This is a descriptive study, the population of this study was 184 respondents with consecutive sampling techniques obtained 100 respondents who were examined. anemia variables using GCHb Easy Touch® brand Blood Test measurements and Grade Point Everage (GPA) variations obtained from the Student Academic Information System. Data analysis uses univariate in the form of frequency distribution. Results: The characteristics of respondents in this study were 14 male respondents and 86 female respondents consisting of students in Semester 2 (26%), Semester 4 (44%) and semester 3 (30%). From the results of hemoglobin examination in the blood, data were obtained on 6% of respondents who had mild anemia and the majority of Student Achievement Index was in the high category of 80%. Conclusion: The incidence of anemia in this study was relatively small with the majority cumulative grade point average being high